Prevention and control of sewer system overflows - Water Environment Federation. Prevention and Control of Sewer System Overflows Task Force (New York : McGraw-Hill, 2011)
'The purpose of this Manual of Practice is to provide the information necessary to help managers and engineers understand and analyze an overflow problem (dry weather, CSO [combined sewer overflows], or SSO [sewer system overflows]) and provide guidance in finding the best strategies to reduce or eliminate it. It is also intended to serve as a planning guide in developing long-term control plans for CSOs and SSOs.' -- p. xxxi.
Includes bibliographical references (p. 403-407) and index.
Keywords: Combined sewer overflows -- Environmental aspects; Water -- Pollution -- Prevention